Taxpayer Behavior Towards Fixed Asset Revaluation - Ida Farida Adi Prawira; Memen Kustiawan; Fitri Anggrayni (Future Science, 2020)
The development of tax incentive policies designed to suit the interests and prevailing tax laws and regulations so that this research is directed at identifying, analyzing, and designing effective tax incentive policies. This study aims to describe how taxpayers' behavior towards their decisions in fixed asset revaluation.This study is descriptive in nature, using the Research and Development approach through exploratory studies. This research is not designed to test hypotheses, but describes the data, facts and trends that occur, then analyzed and recommended what kind of Fixed Asset Revaluation policy model should be made to increase taxpayer compliance which can then increase tax revenue. Data obtained by interview techniques, with respondents consisting of corporate taxpayers and experts in the field of Asset Valuation Accounting. The research was conducted for 6 months, data collection was carried out in Bandung. The results of the research aim to be used as input for the Directorate General of Taxes in making tax incentive policies in Fixed Asset Revaluation.